POLARIZATION AND BISPECTRA OF MICROSEISMS OBSERVED AT THE BOROVOE GEOPHYSICAL OBSERVATORY - Aleksandrov S.I.; Pavlenko O.V.; Malyshev Yu.K. (My University, 2001)
Results are presented from an analysis of the polarization and bispectra of microseisms recorded during a 1-day noise monitoring session conducted at the Borovoe Geophysical Observatory, Kazakhstan. Some information was derived concerning the origin of some microseism radiation flows produced by a variety of manmade and natural sources.